Responses to different doses of PMSG on Embryo Collection in Rats - Bambang Poernomo; Yuhara Sukra (Hemera Zoa, 1992)
The development ability of embryos recovered from LMR - Strain rats (age 3 to 4 months with an average 120 g). embryos recovered from treated animals with 10 and 20 IU PMSG, respectively, were compared with those from control (0 IU). Embryos were collected from uteri on day 4 post coital.Treated groups tended to show an increase willingness to mate comfored to control groups, but a high number of embryos that have degenerated in rats treated with 20 IU PMSG were observed. The experiment suggested, that the dose of PMSG was an important source of variation in embryo production.